Trust and Betrayal in War - Ajduković, Dean; Čorkalo Biruški, Dinka (2004)
In 2002 we set out the study to examine how loss of trust and feeling of betrayal among the participants influenced openness to social reconstruction and readiness for reconciliation after the war and the return of Vukovar to Croatian authority. We conducted an interview study of forty-eight Croat and Serb residents of the city, from three age categories and three levels of education. A major criterion for recruiting a person for the study was that he/she must have had close friends from the other ethnic group before the war and that their relationship has been severed or seriously threatened due to war. Our study shows that distrust and betrayal have paralyzed ethnic relations in Vukovar. A way to move forward could be to create a community-based programs that targeted those former friends who are willing, at the minimum, to meet and talk. Such a program could help former friends, and possibly groups of old friends and acquaintances, by providing them with a safe environment where the risk of emotional rejection would be minimal. Key to the success of the program would be the extent to which both sides would be willing to acknowledge and apologize for past crimes committed in their name, even if the scale of such abuses vary greatly. Any program developed in Vukovar to help re-unite former friends and acquaintances will need to emphasize the need for participants to recognize and respect the losses suffered my members of the other group. Along these lines, an intervention program aimed at facilitating dialogue between former friends and other community members could go a long way toward helping Vukovar on the path to recovery.
Projekt MZOS
ENG